Biomarkers of unstable angina pectoris and yangxin decoction intervention: An exploratory metabonomics study of blood plasma - Yu, Xiao-hong (Medicine (Baltimore), 2017)
BACKGROUND: This study aimed to explore the related metabolic biomarkers and to observe the effects of Yangxin Decoction (YXD) on plasma metabolism of patients with unstable angina (UA). METHODS: In total, 10 patients with UA (intervention group) and 10 healthy participants (control group) were recruited for this study from January 2009 to December 2010. Plasma samples from both groups were analyzed using liquid chromatography mass spectrometry (LC-MS). Principle component analysis (PCA) and partial least squares (PLS) were used to explore the correlations between metabolic markers in patients with UA. RESULTS: The LC-MS results indicated that the serum levels of 5 potential metabolic markers, namely, ceramide, glycocholic acid, allocholic acid, lithocholic acid, and leukotriene (LT) B4, were significantly higher in the intervention group than those in the control group. CONCLUSION: The results of this study demonstrated potential metabolic markers that can be used to distinguish and diagnose patients with UA.